Herbert Brown Ames: Political Reformer and Enforcer - Méthot, Mélanie (Urban History Review / Revue d'histoire urbaine, 2003)
To make a distinction between political and social reform may appear simplistic, especially when one considers that many turn of the century social reformers were advocates of prohibition, temperance, child welfare and they turned to the pursuit of female enfranchisement, to achieve their goals. Yet, for social reformers contemporary critics, there was a distinction between political and social reforms, and in their eyes, the ones that needed to be urgently implemented were the latter. The review of social reformer Herbert Brown Ames' municipal career shows that he chose to focus on political reform. He did not envision reforms that would radically transform society. Instead, he asked those with means to assume what he believed should be their moral and financial responsibilities towards the less fortunate. He still believed in the hierarchy of classes. He emphasized the importance of honest businessmen holding positions of potential authority, stressing that the key to a better society resided in the establishment of a professional, accountable, and "scientific" municipal government made up of men like himself. His attempt at professionalizing the municipal government should be seen as a first effort at creating a bureaucracy. Ames should be remembered as a paternalist philanthropist businessman who advocated political reforms.